Duodenal Leiomyosarcoma Mimicking a Pancreatic Pseudocyst. Issue 1 (1994) - Sperti, C.; Pasquali, C.; Di Prima, F.; Baffa, R.; Pedrazzoli, S.
Abstract : A case of duodenal leiomyosarcoma presenting as a cystic mass is reported. Amylase, tumour markers levels in the cyst fluid and radiological findings suggested an inflammatory pancreatic pseudocyst. Exploratory laparotomy and frozen section examination showed a smooth muscle tumour of the duodenum. Pancreatoduodenectomy with pylorus-preser vation was performed and the patient remained symptom-free at 8 months follow-up.